IDENTIFIKASI KOMPONEN KIMIA EMPAT KELAS MUTU GAHARU (KACANGAN A, TERI B, KAMEDANGAN A DAN KAMEDANGAN B) - Totok K. Waluyo; F. Anwar (Jurnal Penelitian Hasil Hutan, 2012)
Agarwood signifies as one of the non-timber forest products (NIFPs) comodities in Indonesia. The form of agarwood varies, such as lumps, chips, flour, until oil. Agarwood in incense shape will give off smells, if burnt. This experiment aimed to identify chemical components in four grades of agarwood from the best to the lowest i.e. kacangan B, teri B, kamedangan A dan kamedangan B. Identification was performed by extracting the agarwood with acetone solvent, and then the acetone extract was fractionated using gradient column chromatography method with n-bexane-ethyl acetate as eluent. Identification of compounds proceeded using gas chromatography-mass spectrophotometer Results of identification revealed that there were sesquiterpene compounds in the four grades of agarwood (i.e. kacangan B, teri B, kamedangan A and kamedangan B), but kinds of compounds were different from one grade to other. Chromone compounds only existed in 2 grades of agarwood covering kacangan B ubich bad 2 compounds (6-bidroxy-2-methyl-5-nitrochromone), and 3-metaxxymethyl-2,5,5,8a-tetramethyl-6,7,8,8a-tetrabydro-5H-chromone), and kamedangan A with only one compound (2,2-dimethyl-6,7-dimetawcychromone). The presence of sesquiterpene and chromone with particular portion and characteristic in each of those four agarwood grades indicatively bears their role explaining their grades from the best until the lowest.